2021
DOI: 10.1038/s41598-021-89086-7
|View full text |Cite
|
Sign up to set email alerts
|

Matrine treatment reduces retinal ganglion cell apoptosis in experimental optic neuritis

Abstract: Inflammatory demyelination and axonal injury of the optic nerve are hallmarks of optic neuritis (ON), which often occurs in multiple sclerosis and is a major cause of visual disturbance in young adults. Although a high dose of corticosteroids can promote visual recovery, it cannot prevent permanent neuronal damage. Novel and effective therapies are thus required. Given the recently defined capacity of matrine (MAT), a quinolizidine alkaloid derived from the herb Radix Sophorae flavescens, in immunomodulation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…ON, which usually occurs in patients with MS and its animal model, EAE ( Quinn et al, 2011 ; Murphy et al, 2020 ), can cause optic nerve damage and subsequently the death of RGCs ( Moore and Goldberg, 2010 ). It has been recently shown that MAT can limit the inflammation and demyelination of the optic nerve and reduce RGCs apoptosis ( Kang et al, 2021 ). However, the mechanism of this natural alkaloid during this process is still unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ON, which usually occurs in patients with MS and its animal model, EAE ( Quinn et al, 2011 ; Murphy et al, 2020 ), can cause optic nerve damage and subsequently the death of RGCs ( Moore and Goldberg, 2010 ). It has been recently shown that MAT can limit the inflammation and demyelination of the optic nerve and reduce RGCs apoptosis ( Kang et al, 2021 ). However, the mechanism of this natural alkaloid during this process is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…As we reported before, MAT effectively suppresses CNS inflammation, demyelination, and axonal loss in optic nerves, as well as RGC apoptosis in EON (Kang et al, 2021). Briefly, we first induced an animal model of EON in Wister rats and then treated it from day 11 p.i., which resulted in a significant reduction in clinical scores for EAE and mitigation in weight loss in the MAT-treated group compared to saline-treated model rats.…”
Section: Mat Alleviated the Severity Of Optic Neuropathologymentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, various ingredients showed anti-inflammatory activity. Matrine, a quinolizidine alkaloid extracted from Sophora flavescens , has the capacity to effectively suppress experimental autoimmune encephalomyelitis and optic neuritis [ 39 , 40 ]. Oxyberberine prevented lipopolysaccharide-induced acute lung injury and improved colitis [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a clinical case report of a group of COVID-19 patients showed that the effective cure rate of matrine-NaCl treatment for COVID-19 was 100% (Zhang et al 2020c ). In terms of neuroprotection, matrine could reduce the numbers of macrophages, microglia and CD 4+ T cells in experimental autoimmune encephalomyelitis rats by inhibiting NF-κB and MAPK- proteinkinase B (Akt) signaling pathways and mitigating the myelin damage by inhibiting the extravasation of the BBB (Kang et al 2021 ; Luo et al 2021 ; Zhang et al 2013 ).…”
Section: Potential Natural Medicines For Neurological Disorders Of Sa...mentioning
confidence: 99%